Curriculum Reform in Library and Information Science Education by Evidence-based Decision Making / Atsushi Toshimori, Chieko Mizoue and Makoto Matsumoto - Toshimori, Atsushi; Mizoue, Chieko; Matsumoto, Makoto (2011)
The student surveys are conducted to better understand the student‘s views and help restructure curriculum. This article explored characteristics of students of the College of Knowledge and Library Sciences (KLIS) at the University of Tsukuba in Japan. The KLIS conducted two kinds of student surveys in 2009 and 2010: a) a standardized survey and b) internal surveys. The results of the surveys showed many students attended the KLIS to major in library and information sciences. Students expressed a high level of satisfaction with the academic program and the general quality of classes provided. The surveys also revealed that students of the KLIS had confidence in their academic performance during high school and believed they could enter their first-choice college. While few of the younger students were aware of the importance of computer competency, the importance of computer courses becomes more apparent in more senior years, indicated by lower dissatisfaction in higher grades. Based on these student surveys, the KLIS has already reformed its curriculum started in 2007. The authors hope that their ideas will progress by combining a standardized student survey with a specialized one. This will lead to a better understanding of who the students are and what they want, and such efforts can maintain the students‘ high satisfaction levels and their assessment of the high quality of classes.